Which Moments Matter Most? Investigating Boundary Conditions of the Effect of Specific Moments on Overall Evaluations of Customer Experiences - Aleksandar Blečić; Sabine Kuester (Journal of Consumer Behaviour, 2024)
ABSTRACT Customer experience (CE) often occurs as a temporal sequence of events that unfold over time. This research investigates the circumstances under which specific moments in the temporal sequence of a CE, such as the beginning or the end, have a disproportionate effect on customers' overall CE evaluations. Specifically, this research explores two boundary conditions of the effect of specific moments: incident valence and perceived control. The results of three scenario experiments, conducted with consumers in two contexts (hedonic and utilitarian), reveal that negative incidents at the end of a CE disproportionately influence overall CE evaluations across these different service contexts, demonstrating recency effects. However, these recency effects do not occur for positive incidents and are only present for individuals with heightened perceived control. Our findings address recent calls to further explore the role of timing and valence in CE evaluations and provide novel insights into the moderating role of perceived control on the effect of specific moments on overall CE evaluations. This research also offers practical guidance to help managers design more effective CEs.
Keywords: 330